The Identity of Society in Typical Batik Motif Ã¢â‚¬Å“Seluang MudikÃ¢â‚¬Â from Sarolangun-Jambi - Prasetyo, Harry; Iswidayati, Sri; Syakir, Syakir (Universitas Negeri Semarang, 2018)
The patterns of batik are strongly influenced by geographical location of the area of manufacture, the state of environment surrounding, and the flora and fauna. Sarolangun area which travesed by Batang Tembesi river makes people familiar with their natural environment. Seluang fish is small fish that Sarolangun endemic which are often waited its existence by the fishermen because of their habit swimming on the river surface in groups. The purpose of the research is to analyze batik patterns Seluang Mudik in Sarolangun regency, Jambi province. The method used in this research was qualitative with observation, interview, and document study as the technique of data collecting. The data validity used the technique of information triangulation from various sources, methods, and theories. The data analysis was done by data reduction, data presentation, and conclusion or verification. The results show that batik motif Seluang Mudik that has various decoration Seluang fish that together swim to a destination to ease the burden against the flow when they immigrate to upstream. It closely relates to the identity of Sarolangun-Jambi society means the knitted togetherness. This togetherness can be found at the events held in society that always be together. One of them is in Lumbo Biduk event, hand in hand in Baralek event, and so on. Implications given by this research is that it can be beneficial for development of batik, for the society surrounding toward environment, for young generations to recognize culture in Sarolangun and for government to support regional potential.